Photosensitivity of MESFETs on Epitaxy Layers of GaAs with Monocrystalline Silicon Wafer - Novosyadliy, S.P.; Gryga, V.M.; Pavlyshyn, A.V.; Lukovkin, V.M. (Physics and Chemistry of Solid State, 2019)
In this paper described researched essentials and physical mechanisms which determine photosensitivity of MESFET on epitaxy layers of GaAs with monocrystalline silicon wafer under their illumination in impure zone absorption spectrum. Conducted experiments showed that source current changing with the type of deep centers, change of value is determined by two factors: change width of volumetric charge barrier contact layer and width of dipole layer on border section of active heterojunction layer of Si-wafer.